1994
DOI: 10.1111/j.1467-8624.1994.tb00756.x
|View full text |Cite
|
Sign up to set email alerts
|

An Ordinal Pattern Analysis of Four Hypotheses Describing the Interactions between Drug-addicted, Chronically Disadvantaged, and Middle-Class Mother-Infant Dyads

Abstract: This study investigated mother‐infant interactions in 18 dyads. All participants were African American and enrolled in an early intervention program because the infants (2–26 months of age) had developmental disabilities or were at high risk for developmental disability. Some mothers had used drugs during their pregnancy, and all mothers were of low or middle socioeconomic status. Dyads were videotaped interacting at 4 different times, separated by at least 5 months in time. Videotapes were rated in terms of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2000
2000
2002
2002

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
0
4
1
Order By: Relevance
“…Contrary to other studies it was Baxter, & pattern analysis ordinal pattern analysis -Parent-Infant found that only 4 of the 18 dyads Butler of four Interaction Scale showed a mother who was less (1994 [12]) hypotheses N=18 dyads: (PIIS) (I) contingently responsive and Chicago, Ill.…”
Section: Brinker An Ordinal Descriptive/ -Mdi (C)contrasting
confidence: 56%
See 4 more Smart Citations
“…Contrary to other studies it was Baxter, & pattern analysis ordinal pattern analysis -Parent-Infant found that only 4 of the 18 dyads Butler of four Interaction Scale showed a mother who was less (1994 [12]) hypotheses N=18 dyads: (PIIS) (I) contingently responsive and Chicago, Ill.…”
Section: Brinker An Ordinal Descriptive/ -Mdi (C)contrasting
confidence: 56%
“…Literature Search (12) Published literature on the topic was obtained from comprehensive review of relevant research articles using the following databases: Medline, Cumulative Index to Nursing and Allied Health Literature (CINAHL), Psychological Abstracts (PsychINFO), and tracking of citations from published articles. For the search, the following key words were used separately, and in combination: maternal/mother, substance use/abuse, infant/child, and mother-infant/child interaction.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations